2021
DOI: 10.1186/s10195-021-00607-6
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic joint infections and legal disputes: a threat to the future of prosthetic orthopedics

Abstract: Prosthetic joint infections (PJI) represent one of the major problems in orthopedic prosthetic surgery. The incidence of PJIs varies according to the site of intervention, and different published case studies report occurrence at 0.5 to 3.0% in the event of first implants, with a significant greater risk in the case of prosthesis revisions. The diagnosis of prosthetic infections is seldom simple, needing a multi-specialist approach, which includes the accurate collection of patient anamnesis, its clinical eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Again, it depends on the surgical skill of the surgeon to keep the operation time as short as possible in minimally invasive THA, since excessive operation times of more than 180 min. after joint replacement are associated with significant blood loss (more than 800 mL), blood transfusion, excessive tissue trauma, the presence of nosocomial bacterial strains, and failure to follow the rules of asepsis and antisepsis [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, it depends on the surgical skill of the surgeon to keep the operation time as short as possible in minimally invasive THA, since excessive operation times of more than 180 min. after joint replacement are associated with significant blood loss (more than 800 mL), blood transfusion, excessive tissue trauma, the presence of nosocomial bacterial strains, and failure to follow the rules of asepsis and antisepsis [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular septic failures are more likely [ 26 ]. Patient-specific factors are thereby in a complex interaction with surgical specifications, as the implant and technique, and are thus involved in the development of an infection [ 27 ]. Oltean-Dan et al therefore reported a particularly higher risk of FNF patients developing PJI [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found a positive correlation between WBC before surgery and SF scores for PF, BP, GH and PCS. The immune response being known in order to limit infection might influence functional outcomes 36 . The number of platelets also correlated with better BP and vitality scores.…”
Section: Discussionmentioning
confidence: 99%